Globalisation and the struggle over hegemony in a peripheral context: Turkey's membership bid to the European Union. Issue 2 (4th March 2021) - Uzgören, Elif
ABSTRACT: Debating Turkey's membership around the question of whether Turkey would become a member or not— form of integration—is a non-debate given the history of relations that is characterized by 'ups and downs' in the last five decades. Embarking on Gramscian historical materialism, this research debates socio-economic content of ongoing integration. It questions whether there is a hegemonic pro-EU membership and whether there are any alternatives. The analyses rely on interviews conducted at two critical junctures in 2010 and 2017. I shall argue that pro-membership is hegemonic which is contested by two rival class strategies: Ha-vet and neo-mercantilism, none of which stands as an overall alternative. The future trajectory is uncertain. Despite negative tone of the political discourses especially in the post-15th July coup attempt, pro-membership is still hegemonic. Yet, it is becoming more difficult for capital groups to lead through 'moral and intellectual leadership' for an integration model relying on market liberalization (negative integration) without a perspective of membership—without a clear social dimension (positive integration).